Regulatory genomic variants associated with fat traits in Nellore cattle - Garcia, Ingrid Soares (2024)
With the increasing consumption of meat and Brazil\'s growing prominence in the global beef cattle industry, there is a pressing need for research aimed at enhancing meat production and quality, particularly in the Nellore breed, which comprises the majority of the Brazilian herd. To advance our understanding of genetic variants controlling economically important fat-related traits, we integrated RNA-seq and single nucleotide polymorphisms (SNPs) identified in genomic and transcriptomic data to generate a linkage disequilibrium filtered panel of 553,581 variants. Expression quantitative trait loci (eQTL) analysis revealed 36,916 cis-eQTLs and 14,408 trans-eQTLs. Association analysis identified three eQTLs associated with backfat thickness (BFT) and 24 with intramuscular fat (IMF). Six eQTLs were found in open chromatin regions. Subsequently, we selected two genes (TGM5 and DGK-θ) regulated by the eQTLs located in regulatory regions to validate their functions in vitro using RNA interference in murine C2C12 cells. Our findings suggest that TGM5 is associated with myoblast cell proliferation, while DGK-θ is not. The results of the present study allow us to better understand the mechanisms of gene expression involved in regulating economically relevant carcass traits.